Maternal And Neonatal Outcome in Major Degree Placenta Praevia: Maternal And Neonatal Outcome - Shah, Ammara; Sultan, Shahnaz; Burki, Farzana; Mukhtar, Muzhda; Khan, Rakhshinda Inam; Khan, Nabila (Pakistan Journal of Health Sciences, 2025)
Placenta praevia relates to pregnancy complications where the placenta is positioned on, or covers the relevant cervix region thus leading to uncontrolled bleeding as being its major risk. The evaluation of mother and fetus outcomes of primary degree placenta praevia is quite important for constructive management and prevention policies to be put in place. Objective: To measure the incidence of negative fetomaternal outcomes in patients with major degree placenta praevia. Methods: This descriptive cross-sectional study was carried out at the Mardan Medical Complex Mardan in the Department of Obstetrics and Gynaecology from the 21st of October to the 31st of December 2024. The sample population includes 177 pregnant women with major degree placenta praevia who were monitored until delivery and 30 days after the birth of the child. Results: The mean maternal age was 29.25 ± 2.10 years, gestational age was 29.32 ± 1.44 weeks, and weight was 67.08 ± 6.17 kg. Associated maternal morbidity encompassed obstetric hysterectomy (14.1%) and bladder injury (11.3), postpartum hemorrhage (24.3%), sip and gout infections (18.6%), and preterm labor (16.9%) with little relations being observed with maternal factors (p>0.05). Some neonatal outcomes included NICU admission (18.6%), while stillbirth had some numbers reported around (15.8%) along with low Apgar scores (15.3%) where once again no significant associations with maternal factors were found (p>0.05). Conclusion: Clinical patterns indicate elevated risks with severe placenta praevia, which calls for close observation even if no statistically significant relationships have been observed.